Comparative study between 68Ga‐prostate‐specific membrane antigen positron emission tomography and conventional imaging in the initial staging of prostate cancer. Issue 6 (28th August 2018) - Wong, Hui Sze; Leung, John; Bartholomeusz, Dylan; Sutherland, Peter; Le, Hien; Nottage, Michelle; Iankov, Ivan; Chang, Joe H
Abstract: Introduction: The management of prostate cancer has undergone significant advances since the introduction of 68 Ga‐prostate‐specific membrane antigen ( 68 Ga‐PSMA) positron emission tomography (PET) scans. Data on the use of 68 Ga‐PSMA PET scans in the setting of biochemical recurrence is widely available. Data on the use of 68 Ga‐PSMA PET as an initial staging modality, however, is limited. The aim of this retrospective study was to compare the staging of patients with newly diagnosed prostate cancer between 68 Ga‐PSMA PET and current conventional imaging modalities. The potential impact of any change in stage will be analysed. Methods: Details of all patients who underwent 68 Ga‐PSMA PET in South Australia between March 2016 and March 2017 were obtained. One hundred and thirty‐one patients with newly diagnosed prostate cancer who had 68 Ga‐PSMA PET prior to consideration of definitive treatment were included in this study. The stage pre‐ 68 Ga‐PSMA PET (based on conventional imaging) and post‐ 68 Ga‐PSMA PET was recorded. The stage was classified as A – localised disease, B – presence of regional lymphadenopathy, C – oligometastatic disease (up to three metastases) and D – widespread metastases. Management plans were recorded. Results: This study showed that the use of 68 Ga‐PSMA PET resulted in a change of stage in 37 (28%) patients with an upstage in 17 (13%) patients and a downstage in 20 (15%) patients ( P < 0.001). 68 Ga‐PSMA PET excluded oligometastatic disease in 11 (8%) patients who had suspicious oligometastatic disease based on a single conventional imaging modality. These 68 Ga‐PSMA PET findings impacted on management in at least 24 (18%) patients. Conclusion: The use of 68 Ga‐PSMA PET scans in initial staging can have a significant impact on staging and management when compared to current conventional imaging modalities.